2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6347117
|View full text |Cite
|
Sign up to set email alerts
|

A microwave powered injectable neural stimulator

Abstract: An unexpectedly simple implantable device that can achieve wireless neurostimulation consists of a short 1 cm long dipole platinum wire antenna, a Schottky diode, and a pulsed microwave transmitter. Fabricated into a 1 cm long by polyimide tubing, the implant can have a sub-millimeter diameter form factor suited to introduction into tissue by injection. Experiments that chronically implant the device next to a rat sciatic nerve show that a 915 MHz microwave transmitter emitting an average power of 0.5 watts ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Another inductively coupled stimulator that was also designed using a simple rectifier included planar coils of 60 mm in diameter, which is considerably larger than the device presented here (Ha et al, 2012 ). Other stimulators have used higher frequencies for energy transmission, such as a microwave powered stimulator (915 MHz) that measures 10 mm in length and 0.8 mm in diameter (Towe et al, 2012 ). Another recent design uses so-called mid-field coupling at 1.6 GHz, resulting in a device that is about 5 mm in the longest dimension (Ho et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another inductively coupled stimulator that was also designed using a simple rectifier included planar coils of 60 mm in diameter, which is considerably larger than the device presented here (Ha et al, 2012 ). Other stimulators have used higher frequencies for energy transmission, such as a microwave powered stimulator (915 MHz) that measures 10 mm in length and 0.8 mm in diameter (Towe et al, 2012 ). Another recent design uses so-called mid-field coupling at 1.6 GHz, resulting in a device that is about 5 mm in the longest dimension (Ho et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to minimize the amount of voltage that is required to operate an inductively powered neural stimulator, we have developed a simple design that consists only of an antenna to receive inductive power, a diode for rectification, and two electrodes on each of the device for current to flow through in order to excite neurons. Previous studies have explored similar concepts of direct rectification of the received signal, but the devices tend to be large (>1 cm on the longest dimension) (Ha et al, 2012 ; Towe et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…We later discovered that such stimulation method had already been proposed and demonstrated in vertebrates by at least two independent research teams in the 60 s [20,21]. Nevertheless, those studies are barely cited and, in fact, no references to them are found after the 80 s. More recently, also independently, the use of implanted RF diodes as rectifying stimulators powered by radiated electromagnetic fields-rather than through ohmic conductance as we propose-has also been demonstrated [22]. It must be noted, however, that such approach was already shown in studies by Schuder et al in the 60 s [21].…”
Section: Discussionmentioning
confidence: 82%
“…A number of different approaches to the realization of implantable neurostimulators of millimeter size have been proposed that are wirelessly powered by magnetic induction, light, microwave energy, or ultrasound (6)(7)(8)(9)(10). Rather than using stored energy from rechargeable batteries, they directly convert incoming energy transmitted through the body to electrical pulses at bioelectrodes.…”
Section: Introductionmentioning
confidence: 99%